Measurement and Empirical Analysis of Student Engagement with Experiential Learning Activities - Gittings, Lara (Curtin University, 2022)
This thesis developed instruments to measure student engagement at an activity level and used these instruments to investigate determinants of accounting university students’ engagement with Experiential Learning Activities (ELAs). Students were more engaged if they were international, had more past experience with ELAs and had accounting work experience. Additionally, the ELA was more engaging to students if it was authentic, detailed, personally relevant and involved critical thinking, but also depended on the method of facilitation.